Dynamics of pro-market institutions and firm performance - Banalieva, Elitsa R; Cuervo-Cazurra, Alvaro; Sarathy, Ravi (Journal of International Business Studies, 2018)
We analyze how pro-market institutions affect firm performance in emerging markets. Integrating transaction costs and signaling theory, we advance three arguments. First, we separate four dynamic components of pro-market institutions: intensifying and fading pro-market reforms and intensifying and fading pro-market reversals. Second, we propose an asymmetric dynamic view whereby not only intensifying reforms but also fading reversals improve firm performance, while not only fading reforms but also intensifying reversals reduce performance. Finally, we argue that more efficient firms perform better under each of the dynamics. We test these arguments on a sample of 1092 firms from 34 emerging markets during 1998–2011.